The Impacts of the Challenges of Fijian Rural High School Students on Their Academic Achievement - Victor Mafone Alasa; Doreen Kumar (Gagasan Pendidikan Indonesia, 2022)
Globalization and technological revolution have made education a priority for every human being. Policymakers and curriculum specialists have given considerable recognition to the provision of quality education. Even though quality education rests upon multiple factors like environment, social and political climate of a country the impact on academic achievements of students in rural schools cannot be underestimated. Many studies have shown that rural schools were faced with multiple challenges that are unique to their environment, which hampers the provision of quality education. There has been little improvement in students’ performance and educational standards in rural schools. The study used the qualitative research method within the constructivist paradigm. Four research objectives and research questions guided the study. Data were collated from respondents purposively drawn from the five schools in the research context of Bua district Region of Fiji Island in the Northern via on call interviews. The findings of the study revealed that certain student-related challenges, teacher-related challenges, curriculum challenges, school support system and lack of parental involvement and socio-economic status significantly affected academic achievements of rural secondary school students in the research context. In conclusion, it is imperative to use education policies, reforms, and strategies to address student related challenges, teacher related challenges, curriculum challenges, improve school support systems to enhance academic achievements. Parental support and engagement are one of the most significant findings of the study which indicates that there is a need for parents to be actively involved in their children’s education by providing academic support, consistently monitoring performance in school by getting feedback from teachers, showing support in school and community-based programs and ensure that the home environment is made conducive for their children’s learning. Rural school students can excel in academic achievements through provision of quality education